Diseases associated with the extracellular calcium-sensing receptor. - Thakker, R (2004)
The human calcium-sensing receptor (CaSR) is a 1078 amino acid cell surface protein, which is predominantly expressed in the parathyroids and kidney, and is a member of the family of G protein-coupled receptors. The CaSR allows regulation of parathyroid hormone (PTH) secretion and renal tubular calcium reabsorption in response to alterations in extracellular calcium concentrations. The human CaSR gene is located on chromosome 3q21.1 and loss-of-function CaSR mutations have been reported in the hypercalcaemic disorders of familial benign (hypocalciuric) hypercalcaemia (FHH, FBH or FBHH) and neonatal severe primary hyperparathyroidism (NSHPT). However, some individuals with loss-of-function CaSR mutations remain normocalcaemic. In addition, there is genetic heterogeneity amongst the forms of FHH. Thus, the majority of FHH patients have loss-of-function CaSR mutations, and this is referred to as FHH type 1. However, in one family, the causative gene for FHH is located on 19p13, referred to as FHH type 2, and in another family it is located on 19q13, referred to as FHH type 3. Gain-of-function CaSR mutations have been shown to result in autosomal dominant hypocalcaemia with hypercalciuria (ADHH) and Bartter's syndrome type V. CaSR auto-antibodies have been found in FHH patients who did not have loss-of-function CaSR mutations, and in patients with an acquired form (i.e. autoimmune) of hypoparathyroidism. Thus, abnormalities of the CaSR are associated with three hypercalcaemic and three hypocalcaemic disorders.